Evaluation of arsenic concentration to propose the remediation alternative in the Ananea river - Vargas Quea, Marcelino (2023)
This study addresses the problem of arsenic contamination of water from the Ananea River due to artisanal and informal mining. The main objective is to evaluate arsenic contamination of waters of the Ananea River and remediation alternatives, during the 12 months of 2018 to 2019. The results reveal that the concentration of arsenic in water at point P-A located in the Sillacunca lagoon was 0.926 mg/l, 0.527 mg/l, 0.730 mg/l; in sediments 117.475 mg/kg, 74.8 mg/kg, 92.50 mg/kg; at the point of monitoring P-B located in the Ananea River 100 meters upstream confluence with the Lunar de Oro River, the concentration of arsenic in water is 0.422 mg/l, 0.221 mg/l, 0.225 mg/l; in sediments it is 56.73 mg/kg, 26.77 mg/kg, 62.5 mg/kg. The concentration of arsenic in the area of the Sillacunca lagoon and in the area in the Ananea river 100 meters upstream confluence with the Lunar de Oro river presented a higher concentration.